Sono, qualidade de vida e transtornos do humor em profissionais de enfermagem que trabalham em unidades de terapia intensiva pediátrica e neonatal - Guerra, Priscilla Caetano [UNIFESP] (2014)
Introduction: The work of nurses in shift regime in hospitals may have an impact on quality of life, especially those who work in pediatric and neonatal intensive care units (ICU). The evaluation of these factors by standard questionnaires may contribute to a better understanding of their daily work. Objectives: To evaluate throughout questionnaires the following variables in nursing professionals of pediatric and neonatal ICUs: 1) Quality of sleep; 2) Quality of life and 3) Presence of mood disorders. Methods: Teams of nursing professionals, grouped into morning, afternoon and night work shifts, were evaluated by the following questionnaires: Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), Morningness-Eveningness Questionnaire (MEQ), Short Form (36) Heath Survey (SF-36), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), State-Trait Anxiety Inventory (STAI). Results: The study sample was composed by 168 professionals, with a predominance of females (94.05%) and age younger than 40 years (74.31%). About a third of professionals worked for at least 10 years in the job. With respect to the workplace, 79.17% work in the Pediatric ICU and 20.83% on Neonatal ICU. Although it was not observed any statistical significance, the sleep-related questionnaires, PSQI and ESS, showed poor sleep quality and excessive daytime sleepiness for the three shifts. The MEQ questionnaire showed a predominance of professionals with neutral typology, 57.49%. The average obtained in the eight domains of the generic SF-36 questionnaire for the three shifts was up 66 points and, in general, there was no statistical difference (p = 0.121), suggesting no loss on their quality of life. However, in the domain "social aspect" of the night shift, the scores was worse (p <0.007). It was not noticed a significant increase in levels of anxiety and depression according to the BDI, BAI and STAI questionnaires in three shifts. Conclusions: The results suggest that nurses may show sleep problems. However, these professionals do not show lower scores for quality of life or mood disorders. One possible explanation for these findings is that, over time, there is an adaptation to the differentiated workload.